2015
DOI: 10.1016/j.visres.2015.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Efficient saccade planning requires time and clear choices

Abstract: We use eye movements constantly to gather information. Saccades are efficient when they maximize the information required for the task, however there is controversy regarding the efficiency of eye movement planning. For example, saccades are efficient when searching for a single target (Nature, 434 (2005) 387–91), but are inefficient when searching for an unknown number of targets in noise, particularly under time pressure (Vision Research 74 (2012), 61–71). In this study, we used a multiple-target search para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…It may be that fixating targets may be more rewarding than resolving the uncertainty since those targets are being acted upon in the next step, selecting them and receiving a reward. Finally, Ghahghaei and Verghese (2015) noted that the effects of uncertainty become stronger as subjects have longer to make their decisions, and in our context subjects were not under time pressure. Thus, the specific experimental context and the nature of the behavioral goals may need to be taken into account when evaluating the importance of uncertainty in gaze target choice.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…It may be that fixating targets may be more rewarding than resolving the uncertainty since those targets are being acted upon in the next step, selecting them and receiving a reward. Finally, Ghahghaei and Verghese (2015) noted that the effects of uncertainty become stronger as subjects have longer to make their decisions, and in our context subjects were not under time pressure. Thus, the specific experimental context and the nature of the behavioral goals may need to be taken into account when evaluating the importance of uncertainty in gaze target choice.…”
Section: Discussionmentioning
confidence: 60%
“…Uncertainty reduction as a controlling factor in gaze target selection has also been investigated by Ghahghaei and Verghese (2015) and Verghese (2012). In these investigations, subjects performed a search task in noise for multiple targets, and it was observed that subjects choose the most likely location as often as the most uncertain location.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, we consider it unlikely that the present endpoints represent a weighted average of bottom-up and top-down information. When bottomup and top-down information compete for oculomotor control, then the contribution of each is determined by the saccade latency: Early saccades are more strongly drawn toward salience, whereas later saccades are more strongly determined by behavioral goals (Schütz, Trommershäuser, & Gegenfurtner, 2012;Ghahghaei & Verghese, 2015). Moreover, in the experiment by Schütz et al (2012), participants learned to adjust their latencies in order to adjust their endpoints and maximize their outcome over the course of the experiment.…”
Section: Target Selection For Saccade Adaptation In a Double-target Smentioning
confidence: 99%
“…In our current study, saccade latencies were short (171 ms mean latency in experiment 1 and 186 ms for experiment 2) but observers might have still been able to strategize their eye movements due to the presentation of the color cues 500–650 ms prior to the display of the test image (see also, Ghahghaei & Verghese, 2014). In addition, recent studies have also shown that humans can execute a suboptimal strategy when searching for multiple targets during search (Verghese, 2012 but see, Janssen & Verghese, 2013), fail to switch from a saccadic targeting strategy (Beutter et al, 2003; Findlay, 1997) to a center of mass (ideal searcher) strategy when varying the separation between two possible target locations (Morvan & Maloney, 2012), and also depart from optimality when presented with faces with uncommon optimal points of fixations (e.g., mouth, Peterson & Eckstein, 2013b).…”
Section: Discussionmentioning
confidence: 59%